PW 0291 More than just a beating: the burden of injuries due to gender based violence in uganda- a 5 year analysis. (November 2018) - Nuwematsiko, Rebecca; Biribawa, Claire; Kisakye, Angella; Musoke, David; Oporia, Frederick; Paichadze, Nino; Pariyo, George; Kobusingye, Olive; Atuyambe, Lynn
Abstract : Globally, injuries are a growing public health problem; with about five million deaths annually. Gender-Based Violence (GBV) is one of the neglected causes of these injuries that is silently affecting lives of many women and men. In Uganda, 56% of women and 55% of men aged between 15 and 49 years' experience physical violence at some point in life. GBV has fatal and non-fatal consequences that greatly affect one's health and social wellbeing. Despite the increase of GBV, little is known about the resulting injuries in Uganda and the people affected. We therefore set to describe the epidemiology of injuries due to gender based violence in Uganda across five years. We retrospectively analysed injury data from the Health Management Information System (HMIS) regarding Gender-Based Violence in Uganda from 2011 to 2015. The HMIS is a national system for routine collection and reporting of data on key health indicators. Descriptive analysis was done according to regions in Uganda as per the Uganda Demographic and Health Survey 2011. We described injuries due to GBV by place, person and time. Of the total injured patients, 4.97% (n=178 489/3 593 312) presented with injuries due to GBV. Females and patients aged 5 years and above were the most victims at 59.8% and 93.4% respectively. The Northern region presented with the highest number of injuries (20.6%). There was an upward trend of injuries from 2011 up to a peak in 2013. Close to 5% of the Injuries in Uganda are due to GBV affecting people of all ages and presenting more in females. The government should strengthen existing programs to eliminate the root causes of GBV through inter-sectoral collaboration. Reporting of injuries and seeking medical care should be prioritised by the victims with a supportive environment by the government.